Penggunaan Metode Webqual 4.0 Sebagai Alat Ukur Kualitas Layanan Website Pemerintah - Surya Darma Sebayang; Idria Maita; Fitriani Muttakin; Angraini (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
This research aims to evaluate the service quality of the Asahan Regency Government website using the Webqual 4.0 method and identify factors influencing user satisfaction. The study is motivated by the need to enhance the standards of services provided by government websites in the context of E-Government in Indonesia. The Webqual 4.0 method is employed as a tool to measure user satisfaction with the Asahan Regency Government website. This method has proven to be effective in identifying factors that influence user satisfaction across various sectors. The research aims to provide valuable insights to the Asahan Regency Government in improving the quality of their website services. Previous studies utilizing the Webqual 4.0 method have shown that usability, information quality, service interaction, and trust significantly contribute to user satisfaction with government website services. However, further research is needed to apply and test the Webqual 4.0 framework in the context of government website usage in Indonesia. The research methodology encompasses defining research objectives, identifying research variables, formulating research questions, developing research instruments, collecting data through surveys using online and offline questionnaires, analyzing data using SPSS software, interpreting the results of data analysis, and preparing the research report. Data were collected from 32 respondents through questionnaires that assessed the website based on predetermined variables. By identifying the factors that influence user satisfaction, this research is expected to assist the Asahan Regency Government in taking appropriate measures to enhance the quality of their website services. This will create a better user experience, increase public participation in utilizing online government services, and ultimately improve the effectiveness and efficiency of governance